Business Feasibility Study Analysis on Determining the Cost of Production of MSMEs in the LDR Café - Tesalonika Tampubolon; Kristin Natalia Doloksaribu; Riskana Natalia Br Bangun; Rifka Sari Br Surbakti; Heriyati Chrisna (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the business operations of LDR Café by examining the production, sales, and financial aspects. Given the increasingly competitive culinary industry, this study uses a field research methodology that includes observation, questionnaires, and documentation to collect primary and secondary data. The findings of the analysis indicate that non-financial factors, location, building materials, technology, and production processes are important things to consider. The marketing aspect also shows good potential with a significant increase in sales. In terms of finance, this business has been running along with the age of the project for seven years. The suggestions given include the development of more modern production technology, expansion of marketing distribution, and preparation of more detailed financial reports to monitor business performance. This study is expected to provide insight for culinary entrepreneurs in optimizing their businesses amidst tight competition.